Isolation of a structural intermediate during switching of degree of interpenetration in a metal–organic framework1. Issue 8 (14th August 2015) - Aggarwal, Himanshu; Das, Raj Kumar; Bhatt, Prashant M.; Barbour, Leonard J.
<x xml:space="preserve">Abstract</x> A structural intermediate has been isolated for the first time during switching of interpenetration from twofold to threefold in the MOF [Co2(ndc)2(bpy)].